Upaya Penanganan Nyeri Pinggang Pada Ibu Hamil Trimester III - Herawati, Arrisqi, Winarsih Nur Ambarwati, S.Kep., Ns., ETN., M.Kep (2017)
Background: Low back pain is a common disorder, and pregnant woman may have a history of "back pain" in the past. Low back pain often occurs very common in pregnancy, symptoms often occurs between 4-7 months of pregnancy and the pain is usually felt in the lower back, spread to the buttocks and thighs, and sometimes down to the foot as statiska. Objectif:To handling back pain in pregnant women in thirth trimester accordancw with the standards of nursing care. Methods: The method used is that describe or depict nursing care in pregnancy women with the problem of low back pain, with case study approach. Process of data collection direct interviews with patients and families, home visits, perfom a physical examination, observe and make a solution by using a journal or book related. Results: After 3x visits in patients with low back pain (lumbar) in the third trimester pregnant women the problem is resolved and the intervention is stopped. Conclusion:The problem occurs in nursing patients can be resolved and the intervention is stopped.